Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.3390/ijms13056424
|View full text |Cite
|
Sign up to set email alerts
|

CD133-Positive Cells Might Be Responsible for Efficient Proliferation of Human Meningioma Cells

Abstract: Owing to lack of appropriate model systems, investigations of meningioma biology have come to a stop. In this study, we developed a comprehensive digestion method and defined a culture system. Using this method and system, primary meningioma cells in conditioned suspension medium and a hypoxic environment could be amplified in spheres and were passaged for more than ten generations. Meningioma sphere cells were positive for meningioma cell markers and negative for markers of neural cell types. Importantly, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
17
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 19 publications
3
17
1
Order By: Relevance
“…Cells were then cultured in stem cell culture medium for at least 4 hours to recover surface antigens. Cells were then labeled with APC- or PE-conjugated CD133 antibody and sorted by fluorescence-activated cell sorting (FACS) as described previously [33]. CD133-positive cells were designated as GBSCs, which were resuspended in serum-free DMEM/F-12 containing human recombinant N 2 (20 ng/mL; Invitrogen), EGF (20 ng/mL; Invitrogen), and bFGF (20 ng/mL; Gibco) and then seeded in a nonadherent cell culture flask (5 mL per flask) at a density of 5 × 10 6 live cells per flask.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were then cultured in stem cell culture medium for at least 4 hours to recover surface antigens. Cells were then labeled with APC- or PE-conjugated CD133 antibody and sorted by fluorescence-activated cell sorting (FACS) as described previously [33]. CD133-positive cells were designated as GBSCs, which were resuspended in serum-free DMEM/F-12 containing human recombinant N 2 (20 ng/mL; Invitrogen), EGF (20 ng/mL; Invitrogen), and bFGF (20 ng/mL; Gibco) and then seeded in a nonadherent cell culture flask (5 mL per flask) at a density of 5 × 10 6 live cells per flask.…”
Section: Methodsmentioning
confidence: 99%
“…Culture media was changed twice a week, and neurospheres are passaged every 1 or 2 weeks, depending on the growth rate of each sample. Immunofluorescence staining to detect the expression of brain tumor stem cell markers was performed as described previously [33]. …”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we presume that meningioma tumor stem cells may be responsible for these events. According to recent reports, CSC-like cells may be present in meningiomas (13,17,30). Traditionally, Nestin, CD133 and Sox2 are regarded as CSC markers, but they could also be considered specific markers for BTSCs (28).…”
Section: █ Discussionmentioning
confidence: 99%
“…According to Singh et al, 100 CD133+ cells are sufficient to initiate brain tumors in non-obese diabetic (NOD)/severe combined immunodeficient (SCID) mice, whereas 100,000 CD133- (5,6,14,18,19,23,31). Recently, Tang et al successfully isolated meningioma cells from six patients and showed that CD133 expression levels were related to cell proliferation rates (30). Therefore, CD133 is regarded as a specific marker of BTSCs in malignant brain tumors (26).…”
Section: █ Discussionmentioning
confidence: 99%
“…Many tumors have shown to display gene expression signatures characteristic of human embryonic stem cells [8]. There may be stemlike cells in meningiomas [1,9]. Prakash Rath [1] had succeeded in isolating meningioma-initiating cells from atypical meningioma.…”
mentioning
confidence: 99%